Caste, religion and regional differentials in life expectancy at birth in India: cross-sectional estimates from recent National Family Health Survey - Kumari, Meena (BMJ Open, 2020)
OBJECTIVE: Though estimates of longevity are available by states, age, sex and place of residence in India, disaggregated estimates by social and economic groups are limited. This study estimates the life expectancy at birth and premature mortality by caste, religion and regions of India. DESIGN: This study primarily used cross-sectional data from the National Family Health Survey (NFHS-4), 2015–2016 and the Sample Registration System (SRS), 2011–2015. The NFHS-4 is the largest ever demographic and health survey covering 601 509 households and 811 808 individuals across all states and union territories in India. MEASURES: The abridged life table is constructed to estimate the life expectancy at birth, adult mortality ((45)q(15)) and premature mortality ((70)q(0)) by caste, religion and region. RESULTS: Life expectancy at birth was estimated at 63.1 years (95% CI 62.60 -63.64) for scheduled castes (SC), 64.0 years (95% CI 63.25 - 64.88) for scheduled tribes (ST), 65.1 years (95% CI 64.69 - 65.42) for other backward classes (OBC) and 68.0 years (95% CI 67.44 - 68.45) for others. The life expectancy at birth was higher among o Christians 68.1 years (95% CI 66.44 - 69.60) than Muslims 66.0 years (95% CI 65.29 - 66.54) and Hindus 65.0 years (95% CI 64.74 -65.22). Life expectancy at birth was higher among females than among males across social groups in India. Premature mortality was higher among SC (0.382), followed by ST (0.381), OBC (0.344) and others (0.301). The regional variation in life expectancy by age and sex is large. CONCLUSION: In India, social and religious differentials in life expectancy by sex are modest and need to be investigated among poor and rich within these groups. Premature mortality and adult mortality are also high across social and religious groups.